2021
DOI: 10.1177/08853282211018567
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of gelatin-based hydrogels with tunable mechanical properties and modulation on cell–matrix interactions

Abstract: Natural polymer material-based hydrogels normally show inferior mechanical stability and strength to bear large deformation and cyclic loading, therefore their applications in food, biomedical and tissue engineering fields are greatly limited. In this study, gelatin-based hydrogels with remarkable stability, as well as tunable mechanical properties, were prepared via a facile method known as the Hofmeister effect. The higher concentration of potassium sulfatesolution resulted in more dehydration and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…Likewise, as shown in , respectively, which were ~60, ~10, and ~4 times higher than that of the pristine PVA membrane. These results are consistent with those of previous studies showing that the Hofmeister effect has profound effects on improving natural or synthetic hydrophilic polymer-based scaffolds [22][23][24][25]. In addition, the mechanical properties of all hybrid porous membranes were much better than those of the composite PVA membranes.…”
Section: Mechanical Properties Of Polyvinyl Alcohol Pp and Citrate-tr...supporting
confidence: 92%
“…Likewise, as shown in , respectively, which were ~60, ~10, and ~4 times higher than that of the pristine PVA membrane. These results are consistent with those of previous studies showing that the Hofmeister effect has profound effects on improving natural or synthetic hydrophilic polymer-based scaffolds [22][23][24][25]. In addition, the mechanical properties of all hybrid porous membranes were much better than those of the composite PVA membranes.…”
Section: Mechanical Properties Of Polyvinyl Alcohol Pp and Citrate-tr...supporting
confidence: 92%
“…The mechanical properties of the native extracellular matrix (ECM) play a key role in regulating cell behavior during development, healing, and homeostasis. With respect to the biomaterial mechanical signals, it has been demonstrated that manipulating them can promote changes in cell behaviors such as spreading, proliferation, migration, and differentiation [ 50 , 51 ]. Therefore, mimicking the brain ECM microenvironment by engineering hydrogels capable of coping with some mechanical stress from adjacent tissues and maintaining at least a slight elasticity and bendability without collapse or losing their shape may allow for investigation and better understanding of NSC behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, these hydrogels lack the required strength. Consequently, the development of a novel injectable hydrogel with excellent cell proliferation and high strength is crucial for applications of meniscus tissue engineering [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%